Diet, Immunity, and Microbiota Interactions: An Integrative Analysis of the Intestine Transcriptional Response and Microbiota Modulation in Gilthead Seabream (Sparus aurata) Fed an Essential Oils-Based Functional Diet - Firmino, Joana P.; Vallejos-Vidal, Eva; Balebona, M. Carmen; Ramayo-Caldas, Yuliaxis; Cerezo, Isabel M.; Salomón, Ricardo; Tort, Lluis; Estevez, Alicia; Moriñigo, Miguel Ángel; Reyes-López, Felipe E.; Gisbert, Enric (Frontiers in Immunology, 2021)
Essential oils (EOs) are promising alternatives as chemotherapeutics in animal production due to their immunostimulant, antimicrobial and antioxidant properties, without associated environmental or hazardous side-effects. In the present study, the modulation of the transcriptional immune response (microarray analysis) and microbiota (16S rRNA sequencing) in the intestine of the euryhaline fish gilthead seabream (Sparus aurata) fed a dietary supplementation of garlic, carvacrol and thymol EOs was evaluated. The transcriptomic functional analysis showed the regulation of genes related to processes of proteolysis and inflammatory modulation, immunity, transport and secretion, response to cyclic compounds, symbiosis and RNA metabolism in fish fed the EOs-supplemented diet. Particularly, the activation of leukocytes, such as acidophilic granulocytes, were suggested to be the primary actors of the innate immune response promoted by the tested functional feed additive in the gut. Fish growth performance and gut microbiota alpha diversity indices were not affected, while dietary EOs promoted alterations in bacterial abundances in terms of phylum, class and genus. Subtle, but significant alterations in microbiota composition, such as the decrease in Bacteroidia and Clostridia classes, were suggested to participate in the modulation of the intestine transcriptional immune profile observed in fish fed the EOs diet. Moreover, regarding microbiota functionality, increased bacterial sequences associated with glutathione and lipid metabolisms, among others, detected in fish fed the EOs supported the metabolic alterations suggested to potentially affect the observed immune-related transcriptional response. The overall results indicated that the tested dietary EOs may promote intestinal local immunity through the impact of the EOs on the host-microbial co-metabolism and consequent regulation of significant biological processes, evidencing the crosstalk between gut and microbiota in the inflammatory regulation upon administration of immunostimulant feed additives.